Strengthening Understanding of the Love-Based Curriculum (KBC) for Teachers at MI Muhammadiyah Cakru Branch - Sofyan Rofi; Bahar Agus Setiawan; Dahani Kusumawati (Journal Of Humanities Community Empowerment, 2026)
This community service activity was carried out to improve teachers' understanding of the Love-Based Curriculum (KBC) concept, and to help them design learning that is in accordance with the four main pillars, namely hablum minallah, hablum minannas, hablum bi'ah, and hubbul wathan, as well as to overcome implementation obstacles at the madrasah level. These four principles are the foundation for fostering harmonious relationships between humans and God, fellow humans, the environment, and the homeland. These obstacles include limited resources and resistance to change. This activity was implemented using training methods to strengthen teacher competency in implementing the Love-Based Curriculum and also teacher understanding of learning models in its implementation. All teachers have responded positively to this training. They understand that a love-based approach can be an effective strategy for building a more humanistic, character-based, and sustainable education. Thus, this training has contributed to implementing the love-based curriculum (KBC) which has been launched by the Ministry of Religion of the Republic of Indonesia.